Barrier laminates and packaging bags
By using a single-layer barrier layer on the paper substrate, containing a combination of hydroxyl polyurethane, a swellable layered silicate and a cationic resin, the problem of difficult water vapor barrier properties and gas barrier properties in the prior art is solved, and efficient environmental friendliness and environmental protection performance is achieved.
Patent Information
- Application Number
- CN202380026729.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2023-03-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-13
AI Technical Summary
In the prior art, when improving the water vapor barrier properties and gas barrier properties of paper substrates, it is difficult to achieve efficient environmental friendliness, and the amount of the barrier layer is applied is large, which affects environmental protection performance.
A single-layer barrier layer is used, which contains hydroxy polyurethane, swellable layered silicate and cationic resin. The water vapor barrier property and gas barrier property are improved through the maze effect, and the burden on the environment is reduced by reducing the amount of the barrier layer applied.
High water vapor barrier properties and gas barrier properties are achieved with a small amount of barrier layers, reducing the amount of coating of barrier layers, improving the recovery rate of pulp, enhancing biodegradation performance, and reducing the burden on the environment.
Smart Images

Figure BDA0005036298100000301 
Figure BDA0005036298100000311 
Figure BDA0005036298100000321
Abstract
Description
Technical Field
[0001] The present disclosure relates to a barrier laminate and a packaging bag using the barrier laminate. Background Art
[0002] Packaging materials in which gas barrier properties such as oxygen barrier properties and water vapor barrier properties are imparted to paper substrates have been conventionally used in packaging of food, medical products, electronic parts, and the like to prevent the quality of the contents from being deteriorated.
[0003] As a method for imparting water vapor barrier properties and gas barrier properties to a paper substrate, a method of laminating a synthetic resin film or the like having excellent gas barrier properties on the paper substrate is generally used. However, the material obtained by laminating a synthetic resin film or the like on a paper substrate is difficult to recycle the paper, synthetic resin, etc. after use, and there are problems in terms of the environment.
[0004] Therefore, gas barrier materials using paper as a substrate without using synthetic resin films etc. have been developed. For example, Patent Document 1 describes a technique for controlling the hydroxyl group and acid group of a resin used in a gas barrier layer in a paper barrier material having a gas barrier layer and a heat seal layer sequentially provided on a paper substrate.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-138434 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The paper barrier material described in Patent Document 1 has a single-layer barrier layer, which can reduce the amount of plastic material. However, it is not sufficient from the viewpoint of water vapor barrier properties.
[0010] The present disclosure provides a barrier laminate that can achieve both high water vapor barrier properties and gas barrier properties with a small number of layers (for example, even a single barrier layer), thereby reducing the amount of barrier layer applied and reducing the burden on the environment.
[0011] Solutions for solving problems
[0012] <1> A barrier laminate having a barrier layer on at least one surface of a paper substrate, wherein the barrier layer is a single layer and has a water vapor permeability of less than 50 g / m at 40° C. and 90% RH 2 day, the oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2·day·atm or less, and the water vapor permeability of the barrier laminate measured at 40°C and 90%RH in accordance with JIS-Z-0208:1976 is less than 50 g / m 2 ·day, the oxygen permeability at 23°C and 50%RH when the barrier laminate was bonded to the CPP film was 10.0 mL / m 2 ·day·atm or less, and the recovery rate of pulp after re-dissociation of the barrier layer stack is 85% by mass or more.
[0013] <2> The barrier laminate according to <1>, wherein the barrier layer contains hydroxy polyurethane and a swelling layered silicate.
[0014] <3> The barrier laminate according to <2>, wherein the barrier layer further contains a cationic resin.
[0015] <4> A barrier laminate having a barrier layer on at least one surface of a paper substrate, wherein the barrier layer contains a hydroxy polyurethane, a swelling layered silicate, and a cationic resin.
[0016] <5> The barrier laminate according to <3> or <4>, wherein the content of the cationic resin in the barrier layer is 1.0 to 20.0% by mass.
[0017] <6> The barrier laminate according to any one of <2> to <5>, wherein a content ratio of the hydroxy polyurethane in the barrier layer is 30.0 to 80.0% by mass.
[0018] <7> The barrier laminate according to any one of <2> to <6>, wherein a content ratio of the swellable layered silicate in the barrier layer is 5.0 to 30.0% by mass.
[0019] <8> The barrier laminate according to any one of <1> to <7>, wherein the barrier layer further comprises at least one selected from the group consisting of a water-suspended polymer other than hydroxy polyurethane and a water-soluble polymer other than hydroxy polyurethane, the water-suspended polymer comprises at least one selected from the group consisting of a styrene-butadiene copolymer, an acrylic resin, an olefin-unsaturated carboxylic acid copolymer and a polyolefin resin, and the water-soluble polymer comprises at least one selected from the group consisting of a vinyl alcohol polymer, a (meth) acrylic polymer, polyethylene glycol, a water-soluble polyamide, a polyacrylamide, a polyamine, a polycarboxylic acid and a water-soluble cellulose derivative.
[0020] <9> The barrier laminate according to <8>, wherein the total content of the water-suspendable polymer other than hydroxy polyurethane and the water-soluble polymer other than hydroxy polyurethane in the barrier layer is 2.0 to 50.0% by mass.
[0021] <10> The barrier laminate according to any one of <1> to <9>, wherein the barrier laminate further has a heat seal layer on the side on which the barrier layer is laminated, the heat seal layers of the barrier laminate are heat-sealed to each other under the conditions of 150°C, 0.2 MPa, and 1 second to obtain a sample, and the heat seal strength of the sample when the heat seal layers of the barrier laminate are peeled off from each other using a tensile testing machine is 2.0 N / 15 mm or more.
[0022] <11> The barrier laminate according to <10>, wherein the total coating amount of the barrier layer and the heat seal layer is 12 g / m 2 the following.
[0023] <12> The barrier laminate according to any one of <1> to <11>, wherein the barrier laminate has an oxygen permeability of 10.0 mL / m at 23° C. and 85% RH when the barrier laminate is bonded to a CPP film. 2 ·day·atm or less.
[0024] <13> A packaging bag using the barrier laminate according to any one of <1> to <12>. DETAILED DESCRIPTION
[0025] In this specification, "X to Y" indicating a range means "above X and below Y". When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20 to 25°C) / relative humidity 40% to 50% RH.
[0026] At least one embodiment of the present disclosure (hereinafter also referred to as the first embodiment) is a barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer being a single layer, and having a water vapor permeability of less than 50 g / m at 40° C. and 90% RH. 2 ·day, the oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2 ·day·atm or less, and the water vapor permeability of the barrier laminate measured at 40°C and 90% RH in accordance with JIS-Z-0208:1976 is less than 50 g / m 2 ·day, the oxygen permeability at 23°C and 50% RH when the barrier laminate was bonded to a CPP film was 10 mL / m2 ·day·atm or less, and the recovery rate of pulp after re-dissociation of the barrier laminate is 85% by mass or more.
[0027] At least one embodiment of the present disclosure (hereinafter also referred to as the second embodiment) relates to a barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer containing (A) a hydroxy polyurethane, (B) a swellable layered silicate, and (C) a cationic resin. It should be noted that in the second embodiment, even if the barrier layer containing the above-mentioned components (A) to (C) alone exhibits excellent water vapor barrier properties and gas barrier properties, a barrier layer other than the barrier layer may be further included.
[0028] The present inventors have conducted intensive research on a barrier laminate that can achieve both high water vapor barrier properties and gas barrier properties with a small number of layers (for example, even a single barrier layer) and can reduce the amount of barrier layer applied. And, they have found that the above-mentioned technical problems can be solved by making the barrier laminate.
[0029] In the first embodiment, first, the water vapor permeability of the barrier laminate measured under the conditions of 40° C. and 90% RH in accordance with JIS-Z-0208:1976 is less than 50 g / m 2 The water vapor permeability is preferably 40 g / m 2 ·Day or less, more preferably 30g / m 2 ·Day or less, more preferably 20g / m 2 ·day or less, more preferably 15g / m 2 ·Day or less, especially preferably 10g / m 2 ·Day or less, particularly preferably 8g / m 2 The above range indicates that the water vapor barrier property is very high.
[0030] The lower limit is as low as possible, so there is no particular restriction, but it is preferably 0 g / m 2 · More than 1g / m 2 · More than 2g / m 2 · More than 3g / m 2 The water vapor permeability can be controlled, for example, by the thickness of the barrier layer and the selection of the components contained in the barrier layer.
[0031] In addition, the oxygen permeability at 23°C and 50% RH when the barrier laminate was bonded to the CPP film was 10.0 mL / m 2 ·day·atm or less. The oxygen permeability is preferably 8.0 mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, more preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less, particularly preferably 0.5L / m 2 The above range indicates that the oxygen barrier property is very high.
[0032] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more. The oxygen permeability can be controlled by, for example, the thickness of the barrier layer or the selection of the components contained in the barrier layer.
[0033] The barrier laminate has a barrier layer on at least one side of the paper substrate. In the first embodiment, the barrier layer is a single layer. Furthermore, the water vapor permeability of the barrier layer at 40°C and 90% RH is less than 50 g / m 2 ·day.
[0034] The water vapor permeability of the barrier layer is preferably 40 g / m 2 ·Day or less, more preferably 30g / m 2 ·Day or less, more preferably 20g / m 2 ·day or less, more preferably 15g / m 2 ·Day or less, especially preferably 10g / m 2 ·Day or less, particularly preferably 8g / m 2 ·Day or less.
[0035] The lower limit is as low as possible, so there is no particular restriction, but it is preferably 0 g / m 2 · More than 1g / m 2 · More than 2g / m 2 · More than 3g / m 2 ·day or more.
[0036] The water vapor permeability of the barrier layer is measured by the measuring method described in Examples described later.
[0037] In addition, the oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2 ·day·atm or less.
[0038] The oxygen permeability of the barrier layer is preferably 8.0 mL / m2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, more preferably 2.0mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less, more preferably 0.7mL / m 2 ·day·atm or less, particularly preferably 0.5L / m 2 ·day·atm or less.
[0039] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more.
[0040] The oxygen permeability of the barrier layer is measured by the measuring method described in Examples described below.
[0041] In the first embodiment of the present disclosure, the barrier layer satisfies the above-mentioned water vapor permeability and oxygen permeability, indicating that the water vapor barrier property and gas barrier property of the barrier layer single layer are very high. In addition, since the high water vapor barrier property and gas barrier property as described above can be achieved with a single layer, the coating amount of the barrier layer can be reduced, and the product can be lightweight.
[0042] On the other hand, in the second embodiment of the present disclosure, the barrier layer of the barrier laminate contains hydroxy polyurethane, swellable layered silicate and cationic resin, thereby being able to efficiently exhibit the labyrinth effect obtained by the swellable layered silicate. As a result, it is possible to exhibit very high gas barrier properties and water vapor barrier properties, which contributes to solving the above-mentioned technical problems.
[0043] In addition, the recovery rate of pulp after re-dissociation of the barrier laminate can be increased, the biodegradability can be improved, and the barrier laminate that can reduce the burden on the environment can be obtained. Furthermore, the number of layers of the barrier laminate can be reduced, so the generation of bubbles can be suppressed, and the production can be carried out with a small number of steps.
[0044] In the first embodiment, whether the barrier layer is a single layer can be confirmed by making a cross section in a direction perpendicular to the paper plane and observing it with an electron microscope. Alternatively, it can be confirmed by non-destructive observation using X-ray CT (X-ray computed tomography).
[0045] For example, by selecting a material for the barrier layer, the water vapor permeability and the oxygen permeability can be set to the above ranges.
[0046] The recovery rate of pulp after the barrier laminate is re-dissociated is 85% by mass or more. The recovery rate in the above range indicates that the content ratio of pulp in the barrier laminate is high and the recyclability is high. In addition, it shows that the above-mentioned water vapor permeability and oxygen permeability are satisfied and high water vapor barrier properties and gas barrier properties can be achieved with a small coating amount.
[0047] The recovery rate of the pulp is preferably 88% by mass or more, more preferably 90% by mass or more, and even more preferably 92% by mass or more. The upper limit is not particularly limited, but is preferably 99% by mass or less, 98% by mass or less, or 97% by mass or less.
[0048] The recovery rate of the pulp can be controlled by the coating amount of the barrier layer, etc., the content of the layered inorganic compound (swellable layered silicate) in the barrier layer, the basis weight of the paper substrate, and the like.
[0049] Furthermore, when the barrier laminate is bonded to the CPP film, the oxygen permeability at 23°C and 85% RH is preferably 10.0 mL / m 2 ·day·atm or less, more preferably 8.0mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, particularly preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less.
[0050] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more.
[0051] The oxygen permeability at 85% RH satisfies the above range, indicating that sufficient gas barrier properties are exhibited even in a high humidity environment. The oxygen permeability at 85% RH can be set to the above range by selecting a material for the barrier layer.
[0052] Hereinafter, each material of the barrier laminate will be described.
[0053] <Paper base material>
[0054] The barrier laminate includes a paper substrate. The paper substrate is not particularly limited, and a known paper material can be used.
[0055] The pulp constituting the paper substrate preferably has plant-derived pulp as a main component, and wood pulp as a main component. Examples of wood pulp include hardwood pulp and coniferous wood pulp. Examples of non-wood pulp include cotton pulp, hemp pulp, kenaf pulp, and bamboo pulp. Unless the effects of the present invention are impaired, materials other than pulp fibers, such as synthetic fibers such as rayon fibers and nylon fibers, may be used as secondary paper materials.
[0056] Specifically, paper substrates include bleached kraft paper, unbleached kraft paper, fine paper, cardboard, liner, coated paper, single gloss white kraft paper, glassine, and Grafan paper. Among them, bleached kraft paper, unbleached kraft paper, fine paper, and single gloss white kraft paper are preferred. Bleached kraft paper and glossy paper are more preferred, and single gloss white kraft paper is even more preferred.
[0057] Additives may also be added to the paper substrate. Examples of additives include pH adjusters (sodium bicarbonate, sodium hydroxide, etc.), dry strength agents (polyacrylamide, starch, etc.), wet strength agents (polyamide polyamine epichlorohydrin resin, melamine-formaldehyde resin, urea-formaldehyde resin), internal sizing agents (rosin, alkyl ketene dimer, etc.), retention and drainage aids, defoamers, fillers (calcium carbonate, talc, etc.), dyes, etc. These additives may be used alone or in combination of two or more. The content of the additives is not particularly limited and may be within the range commonly used.
[0058] (Weight per unit area)
[0059] The weight per unit area of the paper substrate is not particularly limited, but for example, for packaging bags, it is preferably 20 g / m 2 Above and 150g / m 2 Below, more preferably 30g / m 2 Above and 100g / m 2 Below, more preferably 40g / m 2 Above and 70g / m 2 The basis weight of the paper substrate is measured in accordance with JIS P 8124:2011.
[0060] (Paper thickness)
[0061] The thickness of the paper substrate is not particularly limited, but for example, for packaging bags, it is preferably 20 μm to 150 μm, more preferably 25 μm to 100 μm, and even more preferably 30 μm to 50 μm. The thickness of the paper substrate is measured in accordance with JIS P 8118:2014.
[0062] (Wang Yan type smoothness)
[0063] The smoothness of the paper substrate is not particularly limited. For example, the surface on which the barrier layer is provided preferably has a keratin smoothness of 5 seconds or more, more preferably 10 seconds or more. The upper limit is not particularly limited, but is preferably 2000 seconds or less, more preferably 1000 seconds or less. It should be noted that the keratin smoothness of the paper substrate is measured in accordance with JIS P 8155:2010.
[0064] (Method for producing paper substrate)
[0065] As a method for producing a paper substrate, there can be mentioned a method of making paper from a paper stock containing pulp. It should be noted that the paper stock may further contain additives. As additives, for example, the additives listed above can be mentioned.
[0066] The paper stock can be prepared by adding an additive to a pulp slurry. The pulp slurry is obtained by beating pulp in the presence of water. The pulp beating method and the beating device are not particularly limited, and can be the same as the known beating method and beating device. The content of the pulp in the paper stock is not particularly limited, and can be within the range commonly used. For example, it is 60% by mass or more and less than 100% by mass relative to the total mass of the paper stock.
[0067] Papermaking of paper stock can be carried out by conventional methods. For example, the following methods can be cited: casting the paper stock on a wire or the like, dehydrating to obtain wet paper, overlapping multiple wet paper sheets as needed, pressing the single-layer or multi-layer wet paper sheets, and drying them. In this case, a single-layer paper can be obtained when multiple wet paper sheets are not overlapped, and a multi-layer paper can be obtained when multiple wet paper sheets are overlapped. When overlapping multiple wet paper sheets, an adhesive can also be applied to the surface of the wet paper (the surface overlapping other wet paper sheets).
[0068] <Barrier layer>
[0069] In the first embodiment, the barrier laminate has a single barrier layer on at least one surface of the paper substrate. As described above, the barrier layer exhibits high water vapor barrier properties and gas barrier properties. The material used for the barrier layer is not particularly limited as long as it can exhibit the above-mentioned water vapor barrier properties and gas barrier properties. For example, the following known resins can be used.
[0070] Examples of the resin that can be used for the barrier layer include polyolefin resins (polyethylene, polypropylene, etc.), vinyl chloride resins, styrene resins, styrene / butadiene copolymers, acrylonitrile / styrene copolymers, acrylonitrile / butadiene copolymers, ABS (acrylonitrile butadiene styrene: acrylonitrile / butadiene / styrene) resins, AAS (acrylonitrile acrylate styrene: acrylonitrile / acrylate / styrene) resins, AES (acrylonitrileethylene propylene rubbers Styrene: acrylonitrile / ethylene propylene rubber / styrene) resin, vinylidene chloride resin, polyurethane resin, poly-4-methylpentene-1 resin, polybutene-1 resin, vinylidene fluoride resin, vinyl fluoride resin, fluororesin, polycarbonate resin, polyamide resin, acetal resin, polyphenylene ether resin, polyester resin (polyethylene terephthalate, polybutylene terephthalate, etc.), polyphenylene sulfide resin, polyimide resin, polysulfone resin, polyethersulfone resin, aromatic polyester resin, polyarylate resin, olefin / unsaturated carboxylic acid copolymer, styrene / unsaturated carboxylic acid copolymer, acrylic resin, polyvinyl alcohol and its modified resin, polyacrylic acid and its salt, cellulose derivatives, starch and its derivatives and other polysaccharide resins, natural rubber, ceramics and other natural thermosetting resins and their modified products, etc.
[0071] (Hydroxy polyurethane)
[0072] In the first and second embodiments, the barrier layer preferably contains hydroxy polyurethane in order to exhibit high water vapor barrier properties and gas barrier properties. Hydroxy polyurethane refers to polyurethane having a hydroxy group.
[0073] The hydroxy value of the hydroxy polyurethane is preferably 100 to 500 mgKOH / g, more preferably 150 to 400 mgKOH / g, and even more preferably 200 to 350 mgKOH / g. The above hydroxy value improves the cohesive force of the hydroxy polyurethane and makes it easier to exhibit high barrier properties.
[0074] The hydroxy polyurethane may have an acid group. The acid value of the hydroxy polyurethane is preferably 50 to 100 mgKOH / g, more preferably 10 to 70 mgKOH / g, and further preferably 15 to 60 mgKOH / g.
[0075] The acid value and hydroxyl value of hydroxy polyurethane can be measured by a titration method in accordance with JIS K 1557:2007.
[0076] As the hydroxy polyurethane, commercially available hydroxy polyurethane can be used, and examples thereof include HPU W-001, HPU W-003, and HPU-W013A (all manufactured by Dainichi Seika Industries, Ltd.).
[0077] The content ratio of the hydroxy polyurethane in the barrier layer is preferably 30.0 to 80.0 mass %, more preferably 40.0 to 75.0 mass %, further preferably 50.0 to 70.0 mass %, further more preferably 55.0 to 68.0 mass %, further preferably 60.0 to 66.0 mass %. By being within the above range, it is easy to further improve the water vapor barrier and gas barrier properties. In addition, if it is within the above range, the strength of the barrier layer is good, and when a heat seal layer is provided on the barrier layer, the heat sealability is good.
[0078] (Water-suspended polymer, water-soluble polymer)
[0079] In the first and second embodiments, the barrier layer preferably further comprises at least one selected from the group consisting of a water-suspended polymer other than hydroxy polyurethane and a water-soluble polymer other than hydroxy polyurethane. The water-suspended polymer and the water-soluble polymer can be selected from the above-mentioned resins that can be used for the barrier layer.
[0080] The water-suspendable polymer other than hydroxy polyurethane preferably contains at least one selected from the group consisting of styrene-butadiene copolymers, acrylic resins, olefin-unsaturated carboxylic acid copolymers, and polyolefin resins.
[0081] The water-soluble polymer other than hydroxy polyurethane preferably includes at least one selected from the group consisting of vinyl alcohol polymers, (meth) acrylic polymers, polyethylene glycol, water-soluble polyamides, polyacrylamides, polyamines, polycarboxylic acids, and water-soluble cellulose derivatives, and more preferably includes at least one selected from the group consisting of vinyl alcohol polymers and (meth) acrylic polymers.
[0082] By using such a water-suspendable polymer or a water-soluble polymer, the film-forming property of the barrier layer can be improved, and the water vapor barrier property and the gas barrier property can be improved.
[0083] When forming a barrier layer by water-based coating, water-soluble polymers have a superior effect of improving film-forming properties compared to water-suspended polymers. Moreover, from the perspective of improving the water resistance of the barrier layer and making the water vapor barrier property better, it is preferred to use a water-suspended polymer in addition to the water-soluble polymer. That is, the barrier layer preferably contains a water-suspended polymer and a water-soluble polymer. At this time, as a water-suspended polymer, an olefin-unsaturated carboxylic acid copolymer is preferred, and an ethylene-(meth)acrylic acid copolymer is more preferred. In addition, as a water-soluble polymer, a vinyl alcohol polymer is preferred.
[0084] The mass-based ratio of the water-suspendable polymer content to the water-soluble polymer content in the barrier layer (water-suspendable polymer: water-soluble polymer) is preferably 20:1 to 1:2, more preferably 10:1 to 2:3, further preferably 5:1 to 3:4, and further preferably 4:1 to 4:5.
[0085] (Water-suspended polymer)
[0086] 《Styrene / butadiene copolymers》
[0087] Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, chlorostyrene, etc., butadiene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc., and other compounds copolymerizable with them.
[0088] As the styrene-based compound, styrene is preferred, and as the butadiene-based compound, 1,3-butadiene is preferred.
[0089] As the styrene-butadiene copolymer, a commercially available styrene-butadiene copolymer may be used. For example, as an acid-modified styrene-butadiene copolymer adhesive, LX407S12 (manufactured by ZEON Corporation of Japan) and the like are exemplified.
[0090] 《Styrene / Acrylic Copolymer》
[0091] Styrene / acrylic acid copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, and chlorostyrene and acrylic acid compounds such as acrylic acid, methacrylic acid, (meth)acrylic acid esters, (meth)acrylamide propanesulfonic acid, (meth)acrylic acid sulfoalkyl ester sodium salt (the number of carbon atoms of the alkyl group is 2 or more and 3 or less), and other compounds copolymerizable with them. As the styrene compound, styrene is preferred, and as the acrylic acid compound, acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are preferred, and acrylic acid and acrylic acid esters are more preferred. As the (meth)acrylic acid esters, acrylic acid alkyl esters are preferred, and the number of carbon atoms of the alkyl group is preferably 1 to 6.
[0092] As the styrene / acrylic acid-based copolymer, a commercially available styrene / acrylic acid-based copolymer may be used. For example, as a styrene-acrylic acid copolymer adhesive, JONCRYL HSL-9012 (manufactured by BASF) and the like are exemplified.
[0093] 《Olefin / unsaturated carboxylic acid copolymer》
[0094] The olefin / unsaturated carboxylic acid copolymer is a copolymer obtained by emulsion polymerization of monomers consisting of an olefin, especially an α-olefin such as propylene or ethylene, and an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenetricarboxylic acid, an unsaturated polycarboxylic acid alkyl ester having at least one carboxyl group such as monoethyl itaconate, monobutyl fumarate and monobutyl maleate, and other compounds copolymerizable with them.
[0095] As the olefin, ethylene or α-olefin is preferred, and ethylene is more preferred. In addition, as the unsaturated carboxylic acid monomer, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, etc. are preferred.
[0096] Specific examples of olefin / unsaturated carboxylic acid copolymers include aqueous dispersions of ethylene-acrylic acid copolymer ammonium salts, which are commercially available as ZAIKTHENE (registered trademark) AC (acrylic acid copolymerization ratio 20%, manufactured by Sumitomo Seika Chemicals Co., Ltd.), and are easily available and usable.
[0097] 《Polyolefin resin》
[0098] As the polyolefin resin, a polymer of ethylene or α-olefin is preferred, and polyethylene is more preferred. Commercially available polyolefins may be used. For example, as the polyolefin resin adhesive, HYDRECT HS (manufactured by DIC Corporation) and the like can be cited.
[0099] (Water-soluble polymer)
[0100] 《Vinyl alcohol polymers》
[0101] Examples of the vinyl alcohol polymer include polyvinyl alcohol. The degree of saponification of the polyvinyl alcohol is preferably 85.0 to 99.5 mol%, more preferably 90.0 to 99.0 mol%. Commercially available polyvinyl alcohols may be used. Examples thereof include EXCEVAL series (manufactured by Kuraray Co., Ltd.).
[0102] 《(Meth)acrylic acid polymers》
[0103] Examples of (meth)acrylic acid polymers include polyacrylic acid, polymethacrylic acid, and salts thereof. Examples of salts include sodium poly(meth)acrylate and ammonium poly(meth)acrylate. Commercially available (meth)acrylic acid polymers may also be used. For example, aqueous solutions of ammonium polyacrylate include Aron A-30 (manufactured by Toagosei Co., Ltd.).
[0104] As the water-soluble polymer, known polyethylene glycol, water-soluble polyamide, polyacrylamide, polyamine, polycarboxylic acid, and water-soluble cellulose derivatives can be used. Examples of polycarboxylic acids include polymaleic acid, acrylic acid-maleic acid copolymer, and polyglucuronic acid.
[0105] Examples of the water-soluble cellulose derivatives include methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, and methyl hydroxyethyl cellulose.
[0106] The weight average molecular weight of the water-suspendable polymer and the water-soluble polymer is preferably 10,000 or more, more preferably 20,000 or more, and preferably 10 million or less, more preferably 5 million or less. The weight average molecular weight of the water-suspendable polymer is measured using gel permeation chromatography (standard substance: polystyrene). The weight average molecular weight of the water-soluble polymer is measured using gel permeation chromatography (standard substance: polyethylene glycol).
[0107] The total content of the water-suspended polymer other than hydroxy polyurethane and the water-soluble polymer other than hydroxy polyurethane in the barrier layer is preferably 2.0 to 50.0% by mass, more preferably 5.0 to 45.0% by mass, further preferably 10.0 to 35.0% by mass, and further more preferably 15.0 to 25.0% by mass. By being within the above range, it is easy to further improve the water vapor barrier and gas barrier properties, and the heat sealability is also better.
[0108] (Layered Inorganic Compounds)
[0109] In the first embodiment, in order to further improve the water vapor barrier property and the gas barrier property, the barrier layer may contain a layered inorganic compound. The layered inorganic compound has a flat plate shape.
[0110] By using a layered inorganic compound in the barrier layer, the flat layered inorganic compound is easily stacked roughly parallel to the plane (surface) of the paper substrate. In this way, since the area without the layered inorganic compound in the plane direction becomes smaller, it is easy to suppress the permeation of water vapor. In addition, since the flat layered inorganic compound exists in a manner arranged parallel to the plane of the paper substrate in the thickness direction, the water vapor in the layer passes through while bypassing the layered inorganic compound, and the maze effect is used to suppress the permeation of water vapor. As a result, the barrier layer easily exhibits excellent water vapor barrier properties.
[0111] The average thickness of the layered inorganic compound is preferably 200 nm or less. The average thickness of the layered inorganic compound is preferably 120 nm or less, more preferably 50 nm or less, further preferably 25 nm or less, and particularly preferably 10 nm or less. The smaller the thickness of the layered inorganic compound, the greater the number of layers of the layered inorganic compound in the barrier layer, and thus a high water vapor barrier property can be exerted. The lower limit of the thickness of the layered inorganic compound is not particularly limited, but is preferably 2 nm or more.
[0112] Here, the average thickness of the layered inorganic compound in the state of being contained in the barrier layer is calculated as follows. An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set to include about 20 to 30 layered inorganic compounds in the picture. The thickness of each layered inorganic compound in the picture is measured. Then, the average value of the obtained thickness is calculated as the average thickness of the layered inorganic compound.
[0113] The average length of the layered inorganic compound is preferably 1 μm or more and 100 μm or less. If the average length is 1 μm or more, the layered inorganic compound is easily arranged in parallel with the paper substrate. In addition, if the average length is 100 μm or less, there is a small possibility that a part of the layered inorganic compound protrudes from the barrier layer. The average length of the layered inorganic compound is more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 15 μm or less.
[0114] Here, the average length of the layered inorganic compound in the state of being contained in the barrier layer is calculated as follows. An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set so that the screen contains about 20 to 30 layered inorganic compounds. The length of each layered inorganic compound in the screen is measured. Then, the average value of the obtained lengths is calculated as the average length of the layered inorganic compound. It should be noted that the length of the layered inorganic compound is sometimes recorded in terms of particle size.
[0115] The aspect ratio of the layered inorganic compound is preferably 50 or more. If the aspect ratio is 50 or more, it is easy to further improve the water vapor barrier property. The aspect ratio of the layered inorganic compound is preferably 80 or more, more preferably 300 or more, and particularly preferably 500 or more. The larger the aspect ratio, the more the permeation of water vapor is suppressed, and the more the water vapor barrier property is improved. In addition, the larger the aspect ratio, the more the amount of layered inorganic compound added can be reduced. The upper limit of the aspect ratio is not particularly limited. From the perspective of the viscosity of the coating liquid, it is preferably about 10,000 or less, more preferably about 5,000 or less, and further preferably about 2,000 or less. Here, as described above, the aspect ratio refers to an enlarged photograph of the cross section of the barrier layer taken using an electron microscope, and the value obtained by dividing the average length of the obtained layered inorganic compound by its average thickness.
[0116] Specific examples of the layered inorganic compound include micas such as mica group and brittle mica group, bentonite, kaolinite (kaolin mineral), pyrophyllite, talc, smectite, vermiculite, chlorite, brittle chlorite, serpentine, stilpnomelane, and montmorillonite.
[0117] Among them, in particular, from the viewpoint of improving the barrier properties, it is preferred to contain at least one of mica and bentonite, and mica or bentonite is more preferred. Specific examples of mica include synthetic mica (e.g., swelling mica, non-swelling mica), muscovite, sericite, phlogopite, biotite, fluorphlogopite (artificial mica), red mica, sodium mica, vanadium mica, illite, zinc mica, palagonite, brittle mica, etc. In addition, specific examples of bentonite include montmorillonite.
[0118] In the first and second embodiments, the barrier layer preferably contains a swelling layer silicate such as swelling mica as a layered inorganic compound. The barrier layer preferably contains hydroxy polyurethane and a swelling layer silicate. The swelling layer silicate is a layered inorganic compound that is swellable to water, and the layer is easily cleaved by shearing and has a nanometer-level thickness. By combining hydroxy polyurethane and swelling layer silicate, a thin swelling layer silicate with a high aspect ratio is dispersed in the hydroxy polyurethane resin film that originally has high gas barrier performance, thereby utilizing the maze effect to exert higher gas barrier performance.
[0119] Examples of the swelling layered silicate include sodium tetrasilicon mica, sodium hectorite, lithium taeniamite, fluorphlogopite, sodium montmorillonite, and the like.
[0120] The swellable layered silicate is preferably a swellable mica such as sodium tetrasilicon mica. Among commercially available swellable layered silicates, examples of swellable mica include NTO-05 (manufactured by Topy Industries) and Somasif ME300B-4T (manufactured by Katakura & Co-op Agri Corporation).
[0121] The content of the swelling layered silicate in the barrier layer is preferably 5.0 to 30.0 mass %, more preferably 10.0 to 25.0 mass %, and even more preferably 13.0 to 24.0 mass %. When it is within the above range, the water vapor barrier property and the gas barrier property can be further improved.
[0122] (Cationic resin)
[0123] In the first and second embodiments, the barrier layer preferably contains a cationic resin in addition to the hydroxy polyurethane and the swelling layered silicate. The barrier layer contains a cationic resin, thereby significantly improving the gas barrier property and water vapor barrier property, especially the water vapor barrier property, and easily achieving the above-mentioned specific range of oxygen permeability and water vapor permeability.
[0124] The particle surface of the swelling layer silicate is easily charged to anionicity, and the particle end face is easily charged to cationicity, so the surface and the end face attract each other and easily form a card-house cohesive structure. By adding a cationic resin, the anionic groups on the particle surface can be blocked with cations, and the card-house cohesive structure can be destroyed. Therefore, the three-dimensional cohesion of the swelling layer silicate can be suppressed, and the swelling layer silicate can be arranged parallel to the plane of the paper substrate, and the maze effect can be fully exhibited. As a result, very high gas barrier properties and water vapor barrier properties can be exerted.
[0125] Specific examples of cationic resins include polyalkylene polyamines, polyamide compounds, modified polyamide compounds, polyamide amine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide amine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, polyamide amine polyurea compounds, polyamide amine compounds, polyethyleneimine, polyvinyl pyridine, amino-modified acrylamide compounds, polyvinylamine, polydiallyldimethylammonium chloride, etc.
[0126] Among them, the cationic resin is preferably a modified polyamide compound, and more preferably a modified polyamide resin. As the modified polyamide resin, commercially available modified polyamide resins can be used, and examples thereof include SPI203(50)H and TAOKA CHEMICAL CO., LTD.
[0127] The content of the cationic resin in the barrier layer can be appropriately selected according to the type of materials used for the barrier layer, such as hydroxy polyurethane and swellable layered silicate. From the viewpoint of further improving the barrier properties and / or heat sealability, the content of the cationic resin in the barrier layer is preferably 1.0 to 20.0% by mass, more preferably 1.0 to 10.0% by mass, further preferably 1.5 to 8.0% by mass, further more preferably 1.8 to 5.0% by mass, and particularly preferably 2.0 to 3.0% by mass.
[0128] The surface charge of the cationic resin is preferably 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g, further preferably 0.1 to 4.0 meq / g, further preferably 0.1 to 2.0 meq / g, particularly preferably 0.2 to 1.0 meq / g.
[0129] When the surface charge of the cationic resin is greater than or equal to the above lower limit, the effect of adding the cationic resin can be more fully obtained. On the other hand, when the surface charge is less than or equal to the above upper limit, the aggregation of the swelling layered silicate can be suppressed, and the effect of the cationic resin can be more fully exerted.
[0130] It should be noted that the surface charge of the cationic resin is measured by the following method. First, a polymer as a sample is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. 0.001 N sodium polyvinyl sulfonate is added dropwise to the solution using a charge analyzer Mutek PCD-04 (manufactured by BTG) to measure the charge amount.
[0131] The barrier layer may contain a dispersant, a surfactant, a defoaming agent, a wetting agent, a dye, a color tone adjuster, a thickener, etc. as needed, to such an extent that the above-mentioned specific barrier properties are not impaired.
[0132] (Barrier layer coating amount)
[0133] The coating amount of the barrier layer is not particularly limited, but is preferably 1 g / m 2 as a solid content after drying from the viewpoint of barrier properties. 2 More preferably 2g / m 2 From the viewpoint of re-dissociation, 15 g / m 2 Below, more preferably 10g / m 2 Below, more preferably 8g / m 2 Below, more preferably 6g / m 2 the following.
[0134] The thickness of the barrier layer is preferably 1 to 20 μm, more preferably 2 to 10 μm.
[0135] (Method for forming barrier layer)
[0136] The method for forming the barrier layer is not particularly limited. For example, a barrier layer coating liquid is prepared by dispersing at least one resin selected from the group consisting of water-suspendable polymers and water-soluble polymers other than hydroxy polyurethane, hydroxy polyurethane, swellable layered silicate, and cationic resin in a solvent. Preferably, the obtained barrier layer coating liquid is applied to a paper substrate and dried to form the barrier layer.
[0137] The solvent of the barrier layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not causing the problem of volatile organic solvents, the dispersion medium of the barrier layer coating liquid is preferably an aqueous medium, and more preferably water. In this specification, an aqueous medium refers to a medium containing 50% by mass or more of water.
[0138] The device for applying the barrier layer coating liquid is not particularly limited, and may be appropriately selected from commonly used coating devices. For example, various known coating devices such as an air knife coater, a knife coater, a gravure coater, a rod knife coater, a roll coater, a reverse roll coater, a Meyer rod coater, a curtain coater, a slot coater, a champlex coater, a metering knife-type size press coater, a short dwell coater, a spray coater, a gate roll coater, and a lip coater may be cited.
[0139] <Heat seal layer>
[0140] In the first and second embodiments, the barrier laminate may further include a heat seal layer on the side where the barrier layer is laminated. In the first embodiment, even if the heat seal layer has barrier properties, it is classified as a heat seal layer if it is provided for the purpose of imparting heat seal properties. In the first embodiment, the heat seal layer, for example, does not satisfy the above-mentioned ranges of both water vapor permeability and oxygen permeability of the barrier layer. Alternatively, in the first embodiment, for example, the heat seal layer may satisfy the above-mentioned ranges of either water vapor permeability or oxygen permeability of the barrier layer.
[0141] On the other hand, in the second embodiment, the heat seal layer may have barrier properties such as water vapor barrier properties and gas barrier properties. In the second embodiment, the heat seal layer may also meet at least one or both of the water vapor permeability and oxygen permeability ranges of the barrier layer described above.
[0142] The heat seal layer is a layer that is melted and bonded by heating, ultrasonic waves, etc. The heat seal layer preferably contains a water-dispersible resin. As water-dispersible resins, the above examples can be cited. As water-suspended polymers other than hydroxy polyurethane, preferably, polyolefin resins, styrene / acrylic acid copolymers, ethylene-(meth)acrylic acid copolymers and other acrylic resins, ethylene-vinyl acetate copolymers, polyester resins, rubber resins, polyurethane resins, polyamide resins, etc. can be cited. In addition, in addition to these resins, lubricants such as paraffin wax, carnauba wax, polyolefin wax, and pigments such as silica and kaolin can also be added for the purpose of preventing adhesion and improving oil resistance.
[0143] The heat seal layer is preferably a layer containing a resin, and the resin is preferably at least one resin selected from the group consisting of a styrene / acrylic copolymer and a polyolefin resin. Commercially available materials include styrene acrylate aqueous dispersion (product name: XP8829, manufactured by Starlight PMC), polyolefin aqueous dispersion (product name: Rhobarr320, manufactured by Dow), and the like.
[0144] When the heat seal layer has a barrier property, the water vapor permeability of the heat seal layer at 40° C. and 90% RH is, for example, 1 to 100 g / m2 when converted to a thickness of 20 μm. 2 In addition, the oxygen permeability of the heat seal layer at 23°C and 50% RH is, for example, 1 to 100 mL / m when converted to a thickness of 20 μm. 2 ·day·atm or so.
[0145] (Coating amount of heat seal layer)
[0146] The coating amount of the heat seal layer is not particularly limited, but is preferably 1 g / m 2 as a solid content after drying from the viewpoint of heat sealability. 2 More preferably 2g / m 2 From the viewpoint of re-dissociation, 15 g / m 2 Below, more preferably 10g / m 2 Below, more preferably 8g / m 2 Below, more preferably 6g / m 2 the following.
[0147] The thickness of the heat seal layer is preferably 0.5 to 20 μm, more preferably 1 to 10 μm.
[0148] (Method for forming heat seal layer)
[0149] The method for forming the heat seal layer is not particularly limited. For example, a heat seal layer coating liquid is prepared by dispersing a water-dispersible resin in a solvent. Preferably, the obtained heat seal layer coating liquid is applied to the barrier layer of the paper substrate and dried to form the heat seal layer.
[0150] The solvent of the heat seal layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropanol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not generating the problem of volatile organic solvents, as the dispersion medium of the heat seal layer coating liquid, an aqueous medium is preferred, and water is more preferred.
[0151] The total coating amount of the barrier layer and the heat seal layer is preferably 12 g / m 2 Below, more preferably 11g / m 2The above range means that even a thin layer can exhibit very high gas barrier properties and water vapor barrier properties. In addition, by being within the above range, it is easy to increase the recovery rate of pulp, make the product lighter, and further improve biodegradability.
[0152] The lower limit of the coating amount is not particularly limited, but is preferably 2 g / m 2 More preferably 5g / m 2 More preferably, 8 g / m 2 above.
[0153] The heat seal layers of the barrier laminate are heat-sealed to each other under the conditions of 150° C., 0.2 MPa, and 1 second to obtain a sample, and the heat seal strength when the heat seal layers of the barrier laminate are peeled off using a tensile tester using the sample is preferably 2.0 N / 15 mm or more, more preferably 2.5 N / 15 mm or more, further preferably 2.8 N / 15 mm or more, and further more preferably 3.0 N / 15 mm or more. By setting the heat seal strength within the above range, bag breakage during transport of the contents can be prevented.
[0154] The upper limit is not particularly limited, but is preferably 10.0 N / 15 mm or less, 7.0 N / 15 mm or less, 5.0 N / 15 mm or less, or 4.0 N / 15 mm or less.
[0155] In the first and second embodiments, the barrier laminate may have other layers in addition to the barrier layer and heat seal layer described above. In the second embodiment, the other layer may have barrier properties such as a water vapor barrier layer, a gas barrier layer, or the like.
[0156] <Production of barrier laminate>
[0157] The method for producing the barrier laminate is not particularly limited, and a known method can be used. The method for producing the barrier laminate comprises a step of first applying a barrier layer coating liquid on a paper substrate to form a barrier layer. As required, there may also be a step of applying a heat seal layer coating liquid on the surface of the paper substrate coated with the barrier layer to form a heat seal layer. The formation of each layer is as described above. It should be noted that each layer may be formed by applying and drying the coating liquid one by one, or by applying multiple layers simultaneously and then drying them.
[0158] The drying equipment for drying each coating layer is not particularly limited, and a known equipment can be used. Examples of the drying equipment include a hot air dryer, an infrared dryer, a gas burner, a hot plate, and the like.
[0159] In the first embodiment of the present disclosure, the barrier laminate has a barrier layer on at least one surface of a paper substrate. The barrier laminate preferably has a paper substrate, a barrier layer, and a heat-sealing layer in this order. The barrier laminate may be a laminate consisting only of a paper substrate and a single-layer barrier layer, or may be a laminate consisting only of a paper substrate, a single-layer barrier layer, and a heat-sealing layer.
[0160] A second aspect of the present disclosure provides a barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer containing (A) hydroxy polyurethane, (B) swellable layered silicate, and (C) a cationic resin.
[0161] According to the above embodiment, the extremely high water vapor barrier properties and gas barrier properties obtained by the hydroxy polyurethane, the swellable layered silicate and the cationic resin can be exerted, and the coating amount of the barrier laminate can be suppressed.
[0162] In the second embodiment, the barrier layer containing the above-mentioned (A) to (C) components exhibits excellent water vapor barrier properties and gas barrier properties even if it is a single layer, but it may have two or more layers. In addition, in the second embodiment, when there are other layers (such as a heat seal layer), the other layers may have barrier properties of a water vapor barrier layer, a gas barrier layer, etc. That is, in the second embodiment, the water vapor permeability and oxygen permeability may include the contribution of other layers in addition to the contribution of the barrier layer containing the above-mentioned (A) to (C) components.
[0163] The barrier laminate can be suitably used as a packaging material for food, cosmetics, daily sundries, medical products, electronic components, etc. The barrier laminate has very high water vapor barrier and gas barrier properties, so it can also be suitable as a packaging material for contents with fragrance / odor. In addition, it can also be suitable as a packaging material for food, cosmetics, daily sundries, medical products, electronic components, etc. that are exposed to high humidity conditions. The barrier laminate can be applied to flexible packaging materials such as wrapping paper, packaging bags, covers, labels; liquid containers such as milk cartons; packaging containers such as cups, trays, plates, covers, laminated tubes; etc. The packaged contents can be liquids, solids (granular substances, powders, etc.), and gels.
[0164] [Packaging bag]
[0165] Another embodiment of the present invention is a packaging bag using the barrier laminate. Examples of packaging bags include standing pouch type, side seal type, edge seal type, three-side seal type, four-side seal type, envelope seal type, butt seal type (pillow seal type), pleat seal type, flat bottom seal type, square bottom seal type, gusset type, and the like.
[0166] The packaging bag of the present embodiment may be a packaging bag formed by bending the surface of the barrier laminate having the heat-seal layer or stacking two sheets so that the heat-seal layers face each other and heat-sealing the peripheral edges thereof in the above-mentioned form. In addition, the packaging bag may be a packaging bag formed by bending the barrier laminate or stacking two sheets so that the peripheral edges thereof are bonded with an adhesive in the above-mentioned form.
[0167] [Oxygen permeability at 23°C, 50% RH]
[0168] The oxygen permeability of the barrier laminate was measured using an oxygen permeability measuring device (MOCON OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50%. Specifically, 5 g / m 2 After adding an isocyanate adhesive (manufactured by DIC Corporation, 1 part of DIC dry KW-75 was mixed with 10 parts of DIC dry LX-500), a CPP film (cast polypropylene film: manufactured by Hokuetsu Chemical Co., Ltd., GP-32) having a thickness of 20 μm was laminated to form a laminated sheet.
[0169] For the laminated sheet, the oxygen permeability at a temperature of 23°C and a relative humidity of 50% was measured in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property. It should be noted that the CPP film is laminated so that it is not affected by the unevenness of the laminate and is easy to measure. The CPP film does not affect the oxygen permeability.
[0170] [Oxygen permeability at 23°C, 85% RH]
[0171] The oxygen permeability at 23°C and 85% RH was measured in the same manner as the above-mentioned measurement of the oxygen permeability at 23°C and 50% RH, except that the conditions were changed to 23°C and 85% relative humidity.
[0172] [Water vapor transmission rate]
[0173] The water vapor permeability of the barrier laminates obtained in Examples and Comparative Examples was measured in accordance with JIS-Z-0208:1976 (cup method) B method (40°C ± 0.5°C, relative humidity 90% ± 2%), with the surface provided with the barrier layer facing inward.
[0174] [Oxygen permeability of barrier layer at 23°C, 50% RH]
[0175] The oxygen permeability of the barrier layer in the barrier laminate at 23° C. and 50% RH can be calculated by the following procedure.
[0176] (When materials other than the barrier layer such as the heat seal layer can be obtained)
[0177] For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, and the like.
[0178] Step 1: Measurement of oxygen permeability of barrier laminate The oxygen permeability of the barrier laminate can be measured by the above method.
[0179] Step 2: Analyze the thickness of the heat seal layer. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. The heat seal layer can be coated on a cast polypropylene film or a PET film in such a manner that the thickness of the heat seal layer is measured, and the oxygen permeability in the heat seal layer monomer can be inferred by analogy.
[0180] Step 3: The oxygen permeability of the barrier layer monomer is calculated based on the following formula according to the oxygen permeability of the barrier laminate in step 1 and the oxygen permeability of the heat seal layer monomer in step 2. At this time, regarding the oxygen permeability of the paper substrate, the case where glass paper is not used as the paper substrate (as a benchmark, the total light transmittance of the barrier laminate is less than 60%) can be ignored.
[0181] 1 / P=1 / P1+1 / P2+……+1 / P n
[0182] P: oxygen permeability of the barrier laminate, P1, P2, ... P n : Oxygen permeability of each layer.
[0183] (When materials for layers other than the barrier layer such as the heat seal layer are not available)
[0184] For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, and the like.
[0185] Step 1: Measurement of oxygen permeability of barrier laminate The oxygen permeability of the barrier laminate can be measured by the above method.
[0186] Step 2: Analyze the material and thickness of the heat seal layer. The material of the heat seal layer can be analyzed by pyrolysis GC / MS, FT-IR analysis, Raman spectroscopy analysis, etc. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. The oxygen permeability in the heat seal layer monomer can be inferred based on the material and thickness of the heat seal layer.
[0187] Step 3: The oxygen permeability of the barrier layer monomer is calculated based on the following formula according to the oxygen permeability of the barrier laminate in step 1 and the oxygen permeability of the heat seal layer monomer in step 2. At this time, regarding the oxygen permeability of the paper substrate, the case where glass paper is not used as the paper substrate (as a benchmark, the total light transmittance of the barrier laminate is less than 60%) can be ignored.
[0188] 1 / P=1 / P1+1 / P2+……+1 / P n
[0189] P: oxygen permeability of the barrier laminate, P1, P2, ... P n : Oxygen permeability of each layer.
[0190] [Water vapor permeability of barrier layer]
[0191] The water vapor permeability of the barrier layer of the barrier laminate at 40° C. and 90% RH can be calculated by the following procedure.
[0192] (When materials other than the barrier layer such as the heat seal layer can be obtained)
[0193] For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. (analysis method).
[0194] Step 1: Measurement of water vapor permeability of barrier laminate The water vapor permeability of the barrier laminate can be measured by the above-mentioned method.
[0195] Step 2: Analyze the thickness of the heat seal layer. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. The heat seal layer can be coated on a cast polypropylene film or a PET film in such a manner that the thickness of the heat seal layer is measured, and the water vapor permeability of the heat seal layer alone can be inferred by analogy.
[0196] Step 3: The water vapor permeability of the barrier layer monomer is calculated based on the following formula from the water vapor permeability of the barrier laminate in step 1 and the water vapor permeability of the heat seal layer monomer in step 2. At this time, regarding the water vapor permeability of the paper substrate, the case where glass paper is not used as the paper substrate (as a benchmark, the case where the total light transmittance of the barrier laminate is less than 60%) can be ignored.
[0197] 1 / P=1 / P1+1 / P2+……+1 / Pn
[0198] P: water vapor permeability of the barrier laminate, P1, P2, ..., Pn: water vapor permeability of each layer.
[0199] (When materials for layers other than the barrier layer such as the heat seal layer are not available)
[0200] For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. (analysis method).
[0201] Step 1: Measurement of water vapor permeability of barrier laminate The water vapor permeability of the barrier laminate can be measured by the above-mentioned method.
[0202] Step 2: Analyze the material and thickness of the heat seal layer. The material of the heat seal layer can be analyzed by pyrolysis GC / MS, FT-IR analysis, Raman spectroscopy analysis, etc. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope, X-ray CT measurement, etc. The water vapor permeability in the heat seal layer monomer can be inferred based on the material and thickness of the heat seal layer.
[0203] Step 3: The water vapor permeability of the barrier layer monomer is calculated based on the following formula from the water vapor permeability of the barrier laminate in step 1 and the water vapor permeability of the heat seal layer monomer in step 2. At this time, regarding the water vapor permeability of the paper substrate, the case where glass paper is not used as the paper substrate (as a benchmark, the case where the total light transmittance of the barrier laminate is less than 60%) can be ignored.
[0204] 1 / P=1 / P1+1 / P2+……+1 / Pn
[0205] P: water vapor permeability of the barrier laminate, P1, P2, ..., Pn: water vapor permeability of each layer.
[0206] [Evaluation of re-dissociation property (pulp recovery rate after re-dissociation)]
[0207] The barrier laminate with an absolute dry weight of 30 g was torn into 3-4 cm squares by hand and immersed in tap water at 20°C overnight. After diluting with tap water to a concentration of 2.5% by mass of the barrier laminate, a TAPPI standard disintegrator (manufactured by Kumagai Riki Co., Ltd.) was used for disintegration treatment at a rotation speed of 3000 rpm for 20 minutes. The obtained pulp slurry was supplied to a flat screen (manufactured by Kumagai Riki Co., Ltd.) with a sieve plate of 6 grids (slit width 0.15 mm) and was finely treated in a water flow of 8.3 L / min.
[0208] The undissociated material remaining on the screen plate was recovered, dried in an oven at 105°C, and the absolute dry weight was measured. The pulp recovery rate was calculated according to the following calculation formula.
[0209] Pulp recovery rate (%) = {absolute dry weight of the barrier laminate used for the test (g) - absolute dry weight of the undissociated material (g)} / absolute dry weight of the barrier laminate used for the test × 100
[0210] [Determination of heat seal peel strength]
[0211] Two sets of barrier laminates were overlapped with the coating layers facing each other, and heat sealed at 150°C, 0.2 MPa, and 1 second using a heat seal tester (manufactured by TESTERSANGYO, TP-701-B). The heat-sealed test piece was left to stand for more than 4 hours in a room at a temperature of 23°C ± 1°C and a humidity of 50% ± 2%. Next, the heat-sealed test piece was cut into 15 mm wide pieces, and a tensile tester (TENSILON universal material testing machine RTC-1250A, manufactured by A&D) was used to perform T-peeling at a tensile speed of 300 mm / min, and the maximum load recorded was taken as the heat seal peel strength (N / 15 mm).
[0212] Example
[0213] In order to specifically explain the present invention, examples are given below, but the present invention is not limited to these examples. It should be noted that, unless otherwise specified, the following operations are performed at 25° C. and a relative humidity of 50% RH. In addition, “parts” and “%” in the examples and comparative examples represent “parts by mass” and “% by mass”, respectively, unless otherwise specified.
[0214] (Example 1)
[0215] To 33.3 parts by mass of an aqueous dispersion of a layered inorganic compound (swellable mica (sodium tetrasilicon mica), average length 6.3 μm, aspect ratio about 1000, thickness about 5 nm, solid content concentration 6 mass %, product name: NTO-05, manufactured by Topy Industries), 6.8 parts by mass of a self-emulsifying emulsion of an ethylene-acrylic acid copolymer (solid content concentration 29.2 mass %, product name: ZAIKTHENE AC, manufactured by Sumitomo Seika Chemicals) were added while stirring, and further 26.7 parts by mass of a self-emulsifying aqueous emulsion of a hydroxy polyurethane (hydroxyl value: 235 mgKOH / g, solid content concentration 30 mass %, product name: HPU-W013A, manufactured by Dainichi Seika Industries) was added and stirred.
[0216] 0.57 parts by mass of a modified polyamide resin (surface charge 0.4 meq / g, solid content 53% by mass, product name: SPI203(50)H, manufactured by Taoka Chemical Industry) as a cationic resin was added thereto and stirred. Furthermore, 0.30 parts by mass of a 25% by mass ammonia solution was added thereto and stirred. Furthermore, dilution water was added to adjust the solid content to 19% by mass to prepare a barrier layer coating solution.
[0217] The barrier layer coating liquid is applied with a solid content of 5 g / m 2 Coated on paper substrate 50g / m 2 One side of the paper (single-gloss white kraft paper, manufactured by OJI F-TEX) was dried at 120°C for 1 minute to form a barrier layer. Furthermore, as a heat seal layer coating liquid, a styrene acrylate aqueous dispersion (solid content concentration 48% by mass, product name: XP8829, manufactured by Starlight PMC) was diluted with water to a solid content concentration of 22% by mass, so that the solid content was 5 g / m 2 The heat seal layer was formed by coating in a manner of 100° C. and drying at 120° C. for 1 minute to obtain a heat sealable barrier laminate. It should be noted that a blower dryer was used to dry each layer.
[0218] The oxygen permeability of the heat seal layer at 23°C and 50% RH exceeds 10.0 mL / m 2 ·day·atm, which does not belong to the barrier layer in the first solution.
[0219] (Example 2)
[0220] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, thereby obtaining a heat-sealable barrier laminate.
[0221] (Example 3)
[0222] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the amount of swelling mica in the barrier layer coating liquid was changed to 50 parts by mass, thereby obtaining a heat-sealable barrier laminate.
[0223] (Example 4)
[0224] The paper substrate was set to bleached kraft paper 70g / m 2 (OK bleached kraft paper, manufactured by OJI MATERIA Co., Ltd.), a barrier layer and a heat-seal layer were formed on the paper substrate in the same manner as in Example 1, thereby obtaining a heat-sealable barrier laminate.
[0225] (Example 5)
[0226] A heat-sealable barrier laminate was obtained by forming a barrier layer and a heat-sealable layer on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was replaced with 5.1 parts by mass of a styrene-acrylic acid copolymer adhesive (solid content concentration: 39% by mass, product name: JONCRYL HSL-9012, manufactured by BASF).
[0227] (Example 6)
[0228] The self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 4.3 parts by mass of an acid-modified styrene-butadiene copolymer adhesive (solid content concentration 46% by mass, product name: LX407S12, manufactured by ZEON Corporation of Japan). In the same manner as in Example 1, a barrier layer and a heat-seal layer were formed on the paper substrate to obtain a heat-sealable barrier laminate.
[0229] (Example 7)
[0230] A heat-sealable barrier laminate was obtained by forming a barrier layer and a heat-sealable layer on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was replaced with 8.7 parts by mass of a polyolefin resin adhesive (solid content concentration 23% by mass, product name: HYDRECT HS, manufactured by DIC Corporation).
[0231] (Example 8)
[0232] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating liquid was changed to 1.90 parts by mass, thereby obtaining a heat-sealable barrier laminate.
[0233] (Example 9)
[0234] The self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 20.0 parts by mass of an aqueous solution prepared by dissolving polyvinyl alcohol (product name: EXCEVAL HR-3010, manufactured by Kuraray Co., Ltd.) in water in a manner such that the solid content concentration became 10% by mass. In the same manner as in Example 1, a barrier layer and a heat-seal layer were formed on the paper substrate to obtain a heat-sealable barrier laminate.
[0235] (Example 10)
[0236] The heat seal layer coating liquid was changed to a polyolefin aqueous dispersion (solid content concentration 43% by mass, product name: Rhobarr 320, manufactured by Dow), and a barrier layer and a heat seal layer were formed on the paper substrate in the same manner as in Example 1 to obtain a heat sealable barrier laminate. It should be noted that the water vapor permeability of the heat seal layer at 40°C and 90% RH was 50 g / m 2 · More than one day, and the oxygen permeability at 23°C and 50% RH exceeds 10.0 mL / m 2 ·day·atm, which does not belong to the barrier layer in the first solution.
[0237] (Example 11)
[0238] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 40.0 parts by mass of an aqueous solution prepared by adjusting an aqueous solution of ammonium polyacrylate (solid content concentration 30% by mass, product name: Aron A-30, manufactured by Toagosei Co., Ltd.) to a solid content concentration of 5% by mass, to obtain a heat-sealable barrier laminate.
[0239] (Example 12)
[0240] The amount of added self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 3.4 parts by mass, and polyvinyl alcohol (product name: EXCEVAL HR-3010, manufactured by Kuraray Co., Ltd.) was further dissolved in water in a manner such that the solid content concentration became 10% by mass to obtain a polyvinyl alcohol aqueous solution. 10.0 parts by mass of the polyvinyl alcohol aqueous solution was added to the barrier layer coating liquid. Otherwise, a barrier layer and a heat-seal layer were formed on the paper substrate in the same manner as in Example 10, thereby obtaining a heat-sealable barrier laminate.
[0241] (Example 13)
[0242] The barrier layer coating liquid contained 31.7 parts by mass of the self-emulsifying emulsion of hydroxy polyurethane, 1.7 parts by mass of the self-emulsifying aqueous emulsion of ethylene-acrylic acid copolymer, and 1.90 parts by mass of the cationic resin. The coating amount of the heat seal layer was changed to 3 g / m 2 (converted to solid content), a barrier layer and a heat-seal layer were formed on the paper substrate in the same manner as in Example 10, thereby obtaining a heat-sealable barrier laminate.
[0243] (Example 14)
[0244] A barrier layer was formed on the paper substrate in the same manner as in Example 1, except that the heat seal layer coating liquid was not applied, thereby obtaining a barrier laminate.
[0245] (Example 15)
[0246] The swelling mica in the barrier layer coating liquid was set to 83.3 parts by mass, the cationic resin was set to 5.7 parts by mass, and the coating amount of the heat seal layer was changed to 3 g / m 2 (converted to solid content), a barrier layer and a heat-seal layer were formed on the paper substrate in the same manner as in Example 10, thereby obtaining a heat-sealable barrier laminate.
[0247] (Example 16)
[0248] The amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer added was changed to 5.1 parts by mass, and polyvinyl alcohol (product name: EXCEVAL RS-1717, manufactured by Kuraray Co., Ltd.) was further dissolved in water so that the solid content concentration became 10% by mass to obtain a polyvinyl alcohol aqueous solution. 5.0 parts by mass of the polyvinyl alcohol aqueous solution was added to the barrier layer coating solution, and the coating amount of the heat seal layer was changed to 3 g / m 2 (converted to solid content), a barrier layer and a heat-seal layer were formed on the paper substrate in the same manner as in Example 10, thereby obtaining a heat-sealable barrier laminate.
[0249] (Comparative Example 1)
[0250] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, thereby obtaining a heat-sealable barrier laminate.
[0251] (Comparative Example 2)
[0252] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the swelling mica in the barrier layer coating liquid was 0 parts by mass and the cationic resin was 0 parts by mass, thereby obtaining a heat-sealable barrier laminate.
[0253] (Comparative Example 3)
[0254] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating liquid was changed to 0 parts by mass, thereby obtaining a heat-sealable barrier laminate.
[0255] (Comparative Example 4)
[0256] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating liquid was changed to 18.9 parts by mass, thereby obtaining a heat-sealable barrier laminate.
[0257] (Comparative Example 5)
[0258] A barrier layer and a heat-sealable layer were formed on a paper substrate in the same manner as in Example 1, thereby obtaining a heat-sealable barrier laminate. The barrier layer coating liquid contained 2 parts by mass of kaolin (engineered kaolin, average length 0.89 μm, aspect ratio about 33, thickness about 27 nm, solid content concentration 100% by mass, product name: Contour xtreme, manufactured by Imerys Corporation).
[0259] (Comparative Example 6)
[0260] The barrier layer and the heat-seal layer were formed on the paper substrate in the same manner as in Example 1, except that the self-emulsifying aqueous emulsion of hydroxy polyurethane in the barrier layer coating liquid was changed to 80.0 parts by mass of an aqueous solution of polyvinyl alcohol (product name: EXCEVAL AQ-4104, manufactured by Kuraray Co., Ltd.) dissolved in water in a manner such that the solid content concentration became 10% by mass, to obtain a heat-sealable barrier laminate.
[0261] [Sealing]
[0262] The paper laminates of the examples and comparative examples were formed into pillow-shaped packaging bags and heat-sealed to produce packaging bags. One side of the obtained packaging bags was cut open, and a heat seal check agent (product name: AGELESSseal check, manufactured by Mitsubishi Gas Chemical Co., Ltd., ingredients: high boiling point ester, high boiling point hydrocarbon, vegetable oil, azo oil-soluble dye) was dripped into the packaging bags to evaluate whether there was leakage at the sealed portion.
[0263] A: The heat seal inspection fluid has not leaked and the seal is complete.
[0264] B: The heat seal inspection liquid leaks, resulting in a pinhole and no bonding.
[0265] Tables 1 to 3 show the formulation (mass fraction ratio of solid content), physical properties, evaluation results, oxygen permeability and water vapor permeability of the barrier layer itself, and the content ratio (mass %) of each material in the barrier layer of each obtained barrier laminate.
[0266] In the table, the unit of coating amount is g / m 2 The unit of oxygen permeability is mL / m 2 ·day·atm, the unit of water vapor transmission rate (measured at 40°C and 90% RH) is g / m 2 ·day, the unit of heat seal strength is N / 15mm. The re-dissociation property is the recovery rate (mass %) of pulp after re-dissociation of the barrier laminate.
[0267] In the table, the oxygen permeability of the barrier layer is the oxygen permeability of the barrier layer at 23° C. and 50% RH, and the water vapor permeability of the barrier layer is the water vapor permeability of the barrier layer at 40° C. and 90% RH.
[0268] In the table, regarding the content in the barrier layer, "water-suspendable polymer, etc." indicates the total content ratio of water-suspendable polymers other than hydroxy polyurethane and water-soluble polymers other than hydroxy polyurethane.
[0269] [Oxygen permeability of barrier layer at 23°C, 50% RH]
[0270] The oxygen permeability of the barrier layer monomer was measured using an oxygen permeability measuring device (MOCON, OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50%. Specifically, the barrier layer coating liquid was applied to a paper substrate (single gloss white kraft paper, unit area weight 50 g / m 2 , manufactured by OJI F-TEX Co., Ltd.), and dried at 120°C for 1 minute to form a barrier layer. Then, 5 g / m 2 After adding an isocyanate adhesive (manufactured by DIC Corporation, 1 part of DIC dry KW-75 was mixed with 10 parts of DIC dry LX-500), a CPP film (cast polypropylene film: manufactured by Hokuetsu Chemical Co., Ltd., GP-32) having a thickness of 20 μm was laminated to form a laminated sheet.
[0271] For the laminated sheet, the oxygen permeability at a temperature of 23°C and a relative humidity of 50% was measured in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property. It should be noted that the CPP film is laminated so that it is not affected by the unevenness of the laminate and is easy to measure. The CPP film does not affect the oxygen permeability.
[0272] [Water vapor permeability of barrier layer]
[0273] Regarding water vapor permeability, the barrier layer coating liquid was applied to a paper substrate (single gloss white kraft paper, weight per unit area 50 g / m2) according to the formulation and coating amount of each embodiment / comparative example. 2 , manufactured by OJI F-TEX Co., Ltd.), dried at 120°C for 1 minute to form a barrier layer, and then measured according to JIS-Z-0208:1976 (cup method) B method (40°C±0.5°C, relative humidity 90%±2%) with the side provided with the barrier layer facing inward.
[0274] [Table 1]
[0275]
[0276] [Table 2]
[0277]
[0278] Example 14 did not show adhesion in the measurement of heat seal strength.
[0279] [Table 3]
[0280]
Claims
1. A barrier laminate having a barrier layer on at least one surface of a paper substrate, The barrier layer contains hydroxy polyurethane, swelling layer silicate and cationic resin. The content ratio of the cationic resin in the barrier layer is 1.0 to 10.0% by mass. The barrier layer further comprises at least one selected from the group consisting of a water-suspendable polymer other than hydroxy polyurethane and a water-soluble polymer other than hydroxy polyurethane, The water-suspendable polymer comprises at least one selected from the group consisting of styrene-butadiene copolymers, acrylic resins, olefin-unsaturated carboxylic acid copolymers, and polyolefin resins. The water-soluble polymer includes at least one selected from the group consisting of vinyl alcohol polymers, (meth)acrylic acid polymers, polyethylene glycol, water-soluble polyamides, polyacrylamides, polyamines, polycarboxylic acids, and water-soluble cellulose derivatives.
2. The barrier laminate according to claim 1, wherein The ratio of the content of the water-suspendable polymer to the content of the water-soluble polymer in the barrier layer, that is, water-suspendable polymer:water-soluble polymer, on a mass basis, is 20:1 to 1:
2.
3. The barrier laminate according to claim 1, wherein The water-suspended polymer comprises ethylene-(meth)acrylic acid copolymer, The water-soluble polymer includes a vinyl alcohol copolymer.
4. The barrier laminate according to claim 1, wherein The content ratio of the hydroxy polyurethane in the barrier layer is 30.0 to 80.0% by mass.
5. The barrier laminate according to claim 1, wherein The content ratio of the swelling layered silicate in the barrier layer is 5.0 to 30.0% by mass.
6. The barrier laminate according to claim 1, wherein The total content of the water-suspendable polymer and the water-soluble polymer in the barrier layer is 2.0 to 50.0% by mass.
7. The barrier laminate according to claim 1, wherein The barrier laminate further comprises a heat seal layer on the side where the barrier layer is laminated. The heat seal layers of the barrier laminate are heat-sealed at 150° C., 0.2 MPa, and 1 second to obtain a sample, and the heat seal strength of the sample when the heat seal layers of the barrier laminate are peeled off using a tensile tester is 2.0 N / 15 mm or more.
8. The barrier laminate according to claim 7, wherein The total coating amount of the barrier layer and the heat seal layer is 12 g / m 2 the following.
9. The barrier laminate according to claim 1, wherein The oxygen permeability at 23°C and relative humidity of 85% when the barrier laminate was bonded to a cast polypropylene film was 10.0 mL / m 2 ·day·atm or less.
10. The barrier laminate according to claim 1, wherein The recovery rate of pulp after re-dissociation of the barrier laminate is 85% by mass or more.
11. A packaging bag using the barrier laminate according to any one of claims 1 to 10.
Citation Information
Patent Citations
Packaging paper
JP2021138434A
Gas barrier multilayer body
CN101272904A
Gas-barrier film and process for producing the same
CN102046376A